2018
DOI: 10.1126/scisignal.aaj1676
|View full text |Cite
|
Sign up to set email alerts
|

The β 4 subunit of Ca v 1.2 channels is required for an optimal interferon response in cardiac muscle cells

Abstract: The auxiliary β4subunit of the cardiac Cav1.2 channel plays a poorly understood role in gene transcription. Here, we characterized the regulatory effects of the β4subunit in H9c2 rat cardiac cells on the abundances ofIfnbmRNA [which encodes interferon-β (IFN-β)] and of the IFN-β–related genesDdx58,Ifitm3,Irf7,Stat2,Ifih1, andMx1, as well as on the abundances of the antiviral proteins DDX58, IRF7, STAT2, and IFITM3. Knocking down the β4subunit in H9c2 cells reduced the expression of IFN-β–stimulated genes. In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…To illustrate the Cocl2 and hypoxia-induced intracellular Ca 2+ levels in H9c2 cells in addition to mRNA and protein analysis, we also used the immunofluorescence staining technique for Cav1.1 (1:200), Cav1.2 (1:200), and Cav1.3 (1:200) proteins, by following previous reports with slight modification ( 28 ). Briefly, H9c2 cells were cultured and maintained as described above in 8- chambered cell culture slides (Falcon #08-774-208, Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…To illustrate the Cocl2 and hypoxia-induced intracellular Ca 2+ levels in H9c2 cells in addition to mRNA and protein analysis, we also used the immunofluorescence staining technique for Cav1.1 (1:200), Cav1.2 (1:200), and Cav1.3 (1:200) proteins, by following previous reports with slight modification ( 28 ). Briefly, H9c2 cells were cultured and maintained as described above in 8- chambered cell culture slides (Falcon #08-774-208, Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…VDCC blockers have also been shown to effectively inhibit the infection of the West Nile virus (NWV) and severe fever with thrombocytopenia syndrome virus (SFTSV) by inhibiting the virus-cell fusion step [23,43,44]. The increase in [Ca 2+ ]i produced by certain viruses through VDCCs has also been demonstrated to be necessary for viral replication, and VDCC blockers have proven to be effective antiviral agents against Japanese encephalitis virus (JEV), ZIKV, DENV, and WNV [23,24,45]. It has been shown that Ca 2+ binds to the fusion protein (FP) of MERS-CoV and the 2 FP domains on the S protein of SARS-CoV during the entry stage of both virus types [27,46,47], nevertheless, this phenomenon still requires further investigation.…”
Section: Viral Modifications Of Host Cell Calcium Homeostasismentioning
confidence: 99%
“…It is suggested that ISG15 may play a crucial role in cardiomyocytes infected by SARS-CoV-2. As for another hub gene (MX1), Eshwar et al have shown that the β 4 subunit of Cav1.2 channels can promote the expression of IFN-related genes (including MX1) in cardiomyocytes, thus alleviating viral infection (Tammineni et al 2018). IFIT1, IFIT2, IFIT3 and IFIT5 constitute the human IFIT gene family, which expressed very low in most cell types but can be significantly increased by interferon therapy, viral infection and pathogen-related molecular pattern (PAMP) (Pidugu et al 2019).…”
Section: Discussionmentioning
confidence: 99%